Evaluation of certain mineral salts and microelements against mango powdery mildew under Egyptian conditions - Mostafa, Fatma A.; El Sharkawy, S. A. (Journal of Phytopathology and Disease Management, 2017)
During the two successive seasons 2014 and 2015, three mineral salts used as commercial fertilizers (Potassium di-hydrogen orthophosphate, Potassium bicarbonate (85%), Calcium nitrate (17.1%)) and four microelements (Magnesium sulfate, Iron cheated (Fe-EDTA 6%), Zinc cheated (Zn-EDTA 12%), Manganese cheated (Mn-EDTA 12%)) were evaluated against powdery mildew of mango caused by Oidium mangiferea. Data obtained showed that all materials reduced significantly the disease severity percentage of mango powdery mildew disease comparing the control. Compared fungicides; Topsin M 70 (Thiophanate methyl) and Topas 10% (Penconazole) showed the most superior effect against the disease followed by potassium di-hydrogen orthophosphate. Tested microelements were arranged as zinc, iron and manganese, respectively due to their efficiency. Calcium nitrate and magnesium sulfate revealed the less effect. Evaluated microelements showed the higher efficacy than mineral fertilizers during the two experimental seasons except potassium monophosphate. While, two compared fungicides were the most efficiency to control the disease, tested materials reduced significantly the disease severity of mango powdery mildew disease and showed ability to reduce the number of required applications with conventional fungicides.